2017
DOI: 10.1007/s40430-017-0887-5
|View full text |Cite
|
Sign up to set email alerts
|

An integral method for the boundary layer of MHD non-Newtonian power-law fluid in the entrance region of channels

Abstract: This paper presents the analytical solutions to laminar flow of MHD Newtonian and non-Newtonian power-law fluids in the entrance region of channels. The boundary layer growth and velocity profile of developing flow in a two-dimensional channel, under the influence of a uniform magnetic field, are investigated. The direction of the magnetic field is assumed perpendicular to the flow. For each case, a novel and useful non-dimensional correlation for computing the magnetic entrance length is proposed, using the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…It is observed that there is no variation in the results for 100 × 80 grid. 0.0054 0.0045 Present study (second order) 0.026 0.0156 Present study (third order) 0.042 0.021 Taheri et al [44] (sinusoidal) 0.04 0.0208 Schlichting [47] 0.04 -Hwang et al [35] 0.0422 0.0188 Roidt and Cess [37] 0.0454 0.0167 Bodoia and Osterle [48] 0.044 -Eventually, applying a surface fitted on the datasets, the correlation of the magnetic development length as a function of the Reynolds and Hartmann number is obtained as:…”
Section: Numerical Solutionmentioning
confidence: 86%
See 4 more Smart Citations
“…It is observed that there is no variation in the results for 100 × 80 grid. 0.0054 0.0045 Present study (second order) 0.026 0.0156 Present study (third order) 0.042 0.021 Taheri et al [44] (sinusoidal) 0.04 0.0208 Schlichting [47] 0.04 -Hwang et al [35] 0.0422 0.0188 Roidt and Cess [37] 0.0454 0.0167 Bodoia and Osterle [48] 0.044 -Eventually, applying a surface fitted on the datasets, the correlation of the magnetic development length as a function of the Reynolds and Hartmann number is obtained as:…”
Section: Numerical Solutionmentioning
confidence: 86%
“…For analytical solution, according to the boundary layer approximations, the governing equations including continuity and momentum are defined as [44][45][46]:…”
Section: Governing Equations For Analytical Methods Momentum Integralmentioning
confidence: 99%
See 3 more Smart Citations